Technology of surface wastewater purification, including high-rise construction areas - Tsyba Anna; Skolubovich Yury (E3S Web of Conferences, 2018)
Despite on the improvements in the quality of high-rise construction areas and industrial wastewater treatment, the pollution of water bodies continues to increase. This is due to the organized and unorganized surface untreated sewage entry into the reservoirs. The qualitative analysis of some cities’ surface sewage composition is carried out in the work. Based on the published literature review, the characteristic contamination present in surface wastewater was identified. The paper proposes a new technology for the treatment of surface sewage and presents the results of preliminary studies.